2021
DOI: 10.3390/ijms22168908
|View full text |Cite
|
Sign up to set email alerts
|

Neuropharmacology of Cevimeline and Muscarinic Drugs—Focus on Cognition and Neurodegeneration

Abstract: At present, Alzheimer’s disease (AD) and related dementias cannot be cured. Therefore, scientists all over the world are trying to find a new approach to prolong an active life of patients with initial dementia. Both pharmacological and non-pharmacological pathways are investigated to improve the key symptom of the disease, memory loss. In this respect, influencing the neuromodulator acetylcholine via muscarinic receptors, such as cevimeline, might be one of the therapeutic alternatives. The purpose of this st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 74 publications
(104 reference statements)
0
9
0
Order By: Relevance
“…With the binding of these allosteric modulators, the affinity and/or efficacy of orthosteric (ACh) ligands were affected at the same time ( Bock et al, 2018 ). In addition, the cholinergic system can be therapeutically affected by either direct-acting or indirect-acting cholinergic agents ( Oleksak et al, 2021 ). However, generating ligands with a high degree of selectivity at each muscarinic receptor subtype has been exceptionally challenging ( Thomsen et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…With the binding of these allosteric modulators, the affinity and/or efficacy of orthosteric (ACh) ligands were affected at the same time ( Bock et al, 2018 ). In addition, the cholinergic system can be therapeutically affected by either direct-acting or indirect-acting cholinergic agents ( Oleksak et al, 2021 ). However, generating ligands with a high degree of selectivity at each muscarinic receptor subtype has been exceptionally challenging ( Thomsen et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that clemastine is a MR antagonist, possibly possessing higher affinity toward the M1/M3 receptor than other receptor subtypes ( Kubo et al, 1987 ); in further analyses, the target receptor(s) of clemastine was identified in the OPC culture from M1R–M5R knockout mice and then, the effects of the anti-muscarinic compounds were abolished in MR1-knockout mice, inducing similar numbers of OPCs and differentiated OLs compared to the vehicle-treated M1R-knockout mice, possibly suggesting that M1R could be the most potential mediator of the effects of clemastine on oligodendroglia ( Mei et al, 2016 ), and then the role of clemastine in M1R KO rats with SCI was considered to be explored in our future studies. Cevimeline is a parasympathomimetic and direct-acting MR agonist, usually indicated for treating the symptoms of dry mouth in patients with Sjögren’s syndrome and the therapeutic remedy for treating AD ( Oleksak et al, 2021 ). The toxicity of cevimeline in overdose has not been reported in the medical literature, whereas ingesting high doses of cevimeline (e.g., 30 mg/kg, p.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Originated from Israel Institute of Biological Research, the drug was developed by Daiichi Sankyo company and gained regulatory approval in 2000 for the treatment of dry mouth and Sjögren's syndrome [62]. Recently, the drug has been investigated on such therapeutic areas as cognitive impairment and neurodegenerative diseases [63].…”
Section: Irbesartanmentioning
confidence: 99%